Prediction of regional agro-industrial wastes characteristics by thermogravimetric analysis to obtain bioenergy using thermal process - Saffe Pinto, María Alejandra (2018)
The use of energy from biomass is becoming more common worldwide. This energy source has several benefits that promote its acceptance; it is bio-renewable, non-toxic and biodegradable. To predict its behavior as a fuel during thermal treatment, its characterization is necessary. The experimental determination of ultimate analysis data requires special instrumentation, while proximate analysis data can be obtained easily by using common equipment but, the required time is high. In this work, a methodology is applied based on thermogravimetric analysis, curves deconvolution and empirical correlations for characterizing different regional agro-industrial wastes to determine the high heating value, the contents of moisture, volatiles matter, fixed carbon, ash, carbon, hydrogen, oxygen, lignin, cellulose and hemicellulose. The obtained results are similar to those using standard techniques, showing the accuracy of proposed method and its wide application range. This methodology allows to determine the main parameters required for industrial operation in only in one step, saving time.